Bubbles and Boo - Miles, Ellen (Miles, Ellen. Puppy place., 2016)
When Bubbles, a Poodle, and Boo, a bunny rabbit, arrive at her house for fostering, Lizzie aspires to find a forever home for the fast friends where they can be together.